An essential descriptor for the oxygen evolution reaction on reducible metal oxide surfaces - Tian, Hao (2019)
The development of a universal activity descriptor like the d-band model for transition metal catalysts is of great importance to catalyst design. However, due to the complicated electronic structures of metal oxides, the correlation of the binding energies of reaction intermediates (*OH, *O, and *OOH) in the oxygen evolution reaction (OER) with experimentally controllable properties of metal oxides has not been well established. Here we demonstrate that excess electrons are the essential factor that governs the binding properties of intermediates on the surfaces of reducible metal oxides. We propose that the number of excess electrons (NEE) is an essential activity descriptor toward the OER activities of these oxides, which perfectly reproduces the volcano curve plotted using the descriptor ΔGO − ΔGOH, so that tuning NEE can effectively tailor the OER activities of reducible metal oxide based catalysts. Guided by this descriptor, we predict a novel non-precious catalyst with an overpotential of 0.54 eV, which could be a potential alternative to current Ru or Ir based catalysts.